Redefining Development Resolving Complex Challenges in Developing Countries - Kritz, Jessica (Social Sciences, 2020)
Focuses on the concept phase of the project to resolve complex challenges faced by the communities in the Old Fadama slum of Accra, Ghana. The results are consolidated into a PAR intervention that incorporates results from the process as well as the stakeholders' first strategy, sanitation, and project, latrine and bathhouse installation.